The forming of AISI 409 sheets for fan blade manufacturing - Foroni, F. D.; Menezes, M. A. [UNESP]; Moreira Filho, L. A.; Cueto, E.; Chinesta, F. (Amer Inst Physics, 2007)
The necessity of adapting the standardized fan models to conditions of higher temperature has emerged due to the growth of concern referring to the consequences of the gas expelling after the Mont Blanc tunnel accident in Italy and France, where even though, with 100 fans in operation, 41 people died. The objective of this work is to present an alternative to the market standard fans considering a new technology in constructing blades. This new technology introduces the use of the stainless steel AISI 409 due to its good to temperatures of gas exhaust from tunnels in fire situation. The innovation is centered in the process of a deep drawing of metallic sheets in order to keep the ideal aerodynamic superficies for the fan ideal performance. Through the impression of circles on the sheet plane it is shown, experimentally, that, during the pressing process, the more deformed regions on the sheet plane of the blade can not reach the deformation limits of the utilized sheet material.
Keywords: aeronautic profiles; fan blades; deep-drawing; plastic instability